2011
DOI: 10.1007/s12010-011-9240-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling of Serum from Human Pancreatic Cancer Patients Using 1H NMR Spectroscopy and Principal Component Analysis

Abstract: Pancreatic cancer is a malignant tumor with the worst prognosis among all cancers. At the time of diagnosis, surgical cure is no longer a feasible option for most patients, thus early detection of pancreatic cancer is crucial for its treatment. Metabolomics is a powerful new analytical approach to detect the metabolome of cells, tissue, or biofluids. Here, we report the application of (1)H nuclear magnetic resonance (NMR) combined with principal components analysis to discriminate pancreatic cancer patients fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 20 publications
(17 reference statements)
4
74
1
Order By: Relevance
“…Recently, the possibility of using metabolomics as a diagnostic tool for pancreatic cancer has been investigated in a number of studies (20,27,28,(31)(32)(33)(34). However, in these reports, principle component analysis (PCA) was used to test the use of metabolomics.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the possibility of using metabolomics as a diagnostic tool for pancreatic cancer has been investigated in a number of studies (20,27,28,(31)(32)(33)(34). However, in these reports, principle component analysis (PCA) was used to test the use of metabolomics.…”
Section: Discussionmentioning
confidence: 99%
“…8 To date, several studies have looked at metabolomic profiles in PDAC but have been limited to serum profiling in most cases, and universally applied in late, stage IV disease. 3,[9][10][11][12][13][14][15] The current study was designed to compare metabolomic profiles in urine of patients with early-stage or locally advanced PDAC, with appropriate age and gender-matched, healthy controls. We hypothesize that global metabolite analysis of urine samples using nuclear magnetic resonance (NMR)-based approaches and multivariate statistical techniques will reveal a characteristic metabolomic signature associated with PDAC.…”
mentioning
confidence: 99%
“…the ability to analyze biofluids with high levels of molecular complexity (32). Previous studies have demonstrated the potential for metabolomics as a novel reliable diagnostic approach for hepatocellular carcinoma as well as pancreatic, breast and prostate cancer (18)(19)(20). The few previous investigations into the application of the metabolomic approach on biliary tract cancer consisted of small sample sizes, discrepant results and different methods (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…This novel approach has been demonstrated to be an effective tool for biomarker screening, disease diagnosis and prognosis as well as in the characterization of the metabolic network (14)(15)(16). Metabolomics can be applied to any bio-fluid, including serum, urine, saliva or bile and has been identified as a promising and reliable novel diagnostic approach for several types of tumor, including breast cancer, prostate cancer, hepatocellular carcinoma and pancreatic carcinoma (17)(18)(19)(20). However, few studies have investigated the application of metabolomics in biliary tract cancer or chlangiocarcinoma.…”
Section: Introductionmentioning
confidence: 99%